Consumer Preference-Based Redesign of Vanish Detergent Packaging Using Conjoint Analysis - Rifky Maulana; Muhammad Daffa Fadhlur Rohman; Candra Herawan; Jeims Strong Saragih; Arya Akidnaram; Rizqi Wahyudi (Jurnal Ilmiah Teknik, 2026)
Packaging is an essential component of household cleaning products because it influences consumer convenience, product safety, storage efficiency, and repeated product use. However, detergent packaging redesign based on consumer preferences, especially by integrating functional and ergonomic attributes, remains limited. Objective: This study aims to redesign Vanish detergent packaging by identifying the most influential packaging attributes and determining the optimal packaging configuration using Conjoint Analysis. Methodology: This study used a quantitative approach with Conjoint Analysis. Primary data were collected through questionnaires distributed to 50 respondents who had experience using laundry cleaning products. Five packaging attributes were evaluated: package type, content size, package design, closure system, and ease of use. Consumer preferences were analyzed by estimating utility values and the relative importance of each attribute. Findings: The results showed that the closure system was the most influential attribute, with an importance value of 32%, followed by package type (25%), ease of use (20%), package design (13%), and content size (10%). The ziplock closure system obtained the highest utility value (+1.42), followed by pouch ziplock packaging (+1.18) and bright package design (+0.96). The most preferred packaging configuration was a bright pouch ziplock package with a content size of 900 mL to 1 L and a resealable ziplock closure system. Implications: The findings suggest that detergent packaging redesign should prioritize functional and ergonomic attributes, particularly resealability, practicality, and storage safety, to improve consumer satisfaction and product competitiveness. Originality: This study contributes to packaging design research by applying Conjoint Analysis to identify the optimal combination of functional, ergonomic, and visual attributes for Vanish detergent packaging.